2016
DOI: 10.4103/0301-4738.195011
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of short-term complications and associated factors after primary trabeculectomy in Chiang Mai University Hospital

Abstract: Background:To determine the incidence of early postoperative complications and associated factors after primary trabeculectomy in Thai glaucoma patients.Design:This was a retrospective observational study performed in Chiang Mai University Hospital.Participants:One hundred and eighteen glaucoma patients participated in the study.Methods:All glaucoma patients underwent primary trabeculectomy with mitomycin C (MMC) using fornix-based conjunctival flap technique between December 2011 and May 2013. Surgical compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In this study, 6% had post-operative hypotony while 2% developed choroidal hypotony. The result is consistent with another study conducted in Chiang Mai university hospital, where primary trabeculectomy with mitomycin C was associated with 27.2% hypotony after 3 months of operation (28) .…”
Section: Huang Et Al (2016) Assessing Trabeculotomy In New Bornsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, 6% had post-operative hypotony while 2% developed choroidal hypotony. The result is consistent with another study conducted in Chiang Mai university hospital, where primary trabeculectomy with mitomycin C was associated with 27.2% hypotony after 3 months of operation (28) .…”
Section: Huang Et Al (2016) Assessing Trabeculotomy In New Bornsupporting
confidence: 91%
“…Some studies had reported post-operative long period hypotony with a mean follow up of 53.4 ± 31.4 months (30) . Ahmed valve can detain hypotony and choroidal hypotony to its least (31) .Choroidal hypotony, retinal detachment, hemorrhage are common after cyclo-destructive procedure (17,27,28) . Choroidal detachment was the highest among older patients after trabeculectomy as reported in the Collaborative Initial Glaucoma Treatment Study (CIGTS) (17,27) .…”
Section: Huang Et Al (2016) Assessing Trabeculotomy In New Bornmentioning
confidence: 99%
“…A prospective study found that 1 week after trabeculectomy surgery, 94% and 43% of patients reported a change in their uncorrected and corrected Snellen visual acuity, respectively [ 17 ]. Some studies have attributed these alterations in visual acuity to changes in corneal contour, anterior chamber depth, axial length of the globe, and thickness of the crystalline lens [ 6 , 18 - 23 ]. Another study demonstrated with vector analysis that the cylinder component of refraction was increased by 1.4 D; however, the vector power of surgically induced refractive change at 1 month postoperatively did not significantly correlate with corneal coma-like, spherical-like, or total RMS, suggesting that changes other than anterior corneal aberration, such as internal optics of the eye, play a role in the changes in higher-order aberrations postoperatively[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…49 The large majority of cases will resolve within 7-10 days through medical treatment alone and observation should be directed at restoration of anterior chamber depth, as the choroidal detachment settles itself afterwards. 14,104 Conservative management leads to better visual outcomes. 105 Recovery of the choroidal detachment following treatment occur on average 5.7 days after cessation of topical medication and with steroidal eye drops.…”
Section: Managing Choroidal Detachments In An Optometric Contextmentioning
confidence: 99%